Digital Marketing Kanoko Coffee dalam meningkatkan Brand Image - Ladita Trivira Putri Sjahrina; Riza Hernawati (Bandung Conference Series: Public Relations, 2022)
Abstract. Kanoko Coffee utilizes Instagram social media as digital marketing to increase their brandawareness. The development of today’s media is assisted by the existence of technology which makes this end affect various things. The emergence of social media can make it easier for someone to access information and communicate for daily activities. For that reason, kanoko coffee uses social media as digital marketing very well through its daily content. This study aims to determine how the influence of kanoko coffee’s digital marketing in increasing brandawareness on daily content. The theory used in this research is constructivism theory, marketing theory, new media, digital marketing, digital marketing pr and image. This research methos uses constructivism paradigm, qualitive method with a case study approach. Data collection techniques used are observation and interviews. Abstrak. Kanoko Coffee memanfaaatkan media sosial Instagram sebagai digital marketing untuk meningkatkan brandimage mereka. Berkembangnya media saat ini dibantu dengan adanya teknologi yang membuat akhir ini mempengaruhi berbagai hal. Munculnya media sosial dapat mempermudah seseorang dalam mengakses informasi, bertukar informasi dan berkomunikasi untuk kegiatan sehari- hari. Ma dari itu Kanoko Coffee memanfaatkan media sosial sebagai digital marketing dengan sangat baik melalui daily kontennya. Penelitian ini memiliki tujuan untuk mengetahui bagaimana pengaruh digital marketing Kanoko Coffee dalam meningkatkan brandimage pada daily konten. Teori yang digunakan pada penelitian ini yaitu teori konstruktivisme, new media, pemasaran digital, digital marketing, digital marketing pr dan image. Metode penelitian ini menggunakan peradigma konstruktivisme, metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan yaitu observasi dan wawancara.